PENGARUH PEMBELAJARAN BERBASIS TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SMA PROVINSI JAMBI - Apridzakwan, Hafid; Susanti, Try (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect and magnitude of the impact of Technological Pedagogical Content Knowledge (TPACK)-based instruction on students' critical thinking skills regarding the topic of Environmental Change (Climate Change) for Grade X (Phase E) students at SMAN 11 Muaro Jambi. The study employed a quantitative method using a Pretest-Posttest Control Group Design. The sample consisted of one experimental class receiving TPACK-based instruction and one control class receiving conventional instruction. The research instrument was a critical thinking skills test that had undergone validity and reliability testing. Data analysis included tests for normality and homogeneity, an Independent Sample t-Test, and simple linear regression. The results indicate that TPACK-based instruction had a significant effect on students' critical thinking skills, with a significance value of 0.000 (<0.05). Regression analysis revealed a correlation coefficient (R) of 0.783 and a coefficient of determination (R²) of 0.613, meaning that TPACK-based instruction contributed 61.3% to critical thinking skills, while 38.7% was influenced by other factors. Thus, TPACK-based instruction is effective for enhancing students' critical thinking skills in high school Biology learning.